Inhibitory effects of NSAID-conjugated SN-38 on the viability of A549 Non-small cell lung cancer cells - Hae–Won Kwon; Jusung An; Jong Seung Kim; In-Cheol Kang (Biochemistry and Biophysics Reports, 2023)
The goal of this paper was to look into the anti-tumor mechanism of Non-Steroidal Anti-Inflammatory Drug (NSAID)-conjugated SN-38 Prodrug in A549 lung cancer cells. We found that Indomethacine–SN–38 (IndoSN-38) and Naproxen–SN–38(NaproSN-38) as a theranostic prodrug targeting cyclooxygenase-2(COX-2) in cancer cells inhibited A549 cell viability in a dose-dependent fashion. IndoSN-38 and NaproSN-38 inhibited A549 cell viability in a dose-dependent fashion. The suppression of A549 cell viability was due to induction of the cell apoptosis by enhancing the activities of Caspase 3 and Caspase 8. The cell cycle arrest of sub-G1 was found in the cells treated with IndoSN-38 or NaproSN-38. Collectively, these data suggested that the anti-proliferative activities of the NSAID-conjugated SN-38 prodrugs were due to promotion of cell death and arresting the cell cycle which was similar with those of SN-38.